Factors influencing adherence with subcutaneous immunotherapy among pediatric patient in Surabaya, Indonesia, during and after the COVID-19 pandemic - Pitaloka, Diah Ayu; Endaryanto, Anang; Purnami, Nyilo (Edelweiss Applied Science and Technology, 2025)
Adherence is the most critical issue for subcutaneous immunotherapy (SCIT) as treatment for house dust mite allergy. During the COVID-19 pandemic there was a decline in the attendance at immunotherapy clinics. This study aims to identify factors influencing immunotherapy adherence in Dr. Soetomo’s hospital during and after the pandemic. A retrospective cohort study was conducted between August 2023 and December 2023. The study sample included all patients allergic to house dust mite diagnosed and treated with SCIT under 18 years at the Child Allergy Clinic Facility, Department of Child Health Sciences, Dr. Soetomo General Academic Hospital Surabaya, who were then interviewed using questionnaire and Google Sheet. Data were analyzed using Chi square test with significance set at p<0.05. Structural Equation Modeling (SEM) and Partial Least Squares SEM (PLS-SEM) were used with Smart PLS software. Influencing factors including the risk of systemic reaction, distance to health facilities, injection discomfort, child perception, parental perception, costs and insurance, fears of getting infected with COVID-19, suspected immunotherapy services discontinued, and child positive of COVID-19 are not relate to immunotherapy adherence (p>0.05). Environment factor, including concern about lack of transportation during lockdown and concern relate to family members exposed to COVID-19 influenced immunotherapy adherence.